Friendship : a central moral value - Mitias, Michael H. (Value Inquiry Book Series, 2012)
Friendship was recognized as a central moral value in the classical period, but it was dismissed from medieval, modern, and twentieth century moral theories. This book argues that this dismissal is unjustifiable. The validity of this claim is established in four steps. First, it proposes the concept of moral paradigm. This concept enables us to explore the source of moral value and to provide a criterion for the evaluation of the adequacy of moral theory. Second, the book explains why medieval, modern and twentieth century moral theorists neglected friendship as a central moral value in their analysis of moral behavior and why this neglect was unjustifiable. Third, it explains why the classical moral philosophers viewed friendship as a central moral value. Fourth, it argues that friendship is an ontological need, therefore, a necessary condition of the moral life. This need is implicitly recognized in the moral paradigms that underlie the moral theories of the medieval, modern, and twentieth century moral theories. Accordingly it cannot be neglected in the process of moral theorizing.